STRATEGI MEMENANGKAN PERSAINGAN PADA BISNIS PERCETAKAN DI KOTA PURWOKERTO - Nirmala Nirmala; Cahyaningtyas Ria Uripi (FEB UNWIKU PURWOKERTO, 2020)
The purpose of this study was to identify the strengths, weaknesses, opportunities and threats faced by the real owner of a printing business, as well as formulating business development strategies to increase the capacity of business printing business. This study uses a case study approach with descriptive method qualitative research object on three major printing company in the town of Purwokerto. Data collection techniques using in-depth interviews, observation, focus group discussions (FGD) and literature. The results of the analysis through data reduction is known that the printing business is a business with special characteristics different from other businesses that may be the strengths and opportunities for businesses. Technological progress is an important factor that supports both a strength and a threat to the printing business. In order to win the competition, then the company can undertake a SWOT analysis followed by the formulation of business development strategies.